2014
DOI: 10.1016/j.neurobiolaging.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Widespread age-related differences in the human brain microstructure revealed by quantitative magnetic resonance imaging

Abstract: A pressing need exists to disentangle age-related changes from pathologic neurodegeneration. This study aims to characterize the spatial pattern and age-related differences of biologically relevant measures in vivo over the course of normal aging. Quantitative multiparameter maps that provide neuroimaging biomarkers for myelination and iron levels, parameters sensitive to aging, were acquired from 138 healthy volunteers (age range: 19–75 years). Whole-brain voxel-wise analysis revealed a global pattern of age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
288
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 282 publications
(331 citation statements)
references
References 70 publications
37
288
6
Order By: Relevance
“…The high R2* values for the GP (independent of age) in contrast to thalamus, caudate and putamen are consistent with previous in vivo R2* reports and post-mortem correlations with iron concentration (Gelman et al, 1999;Langkammer et al, 2010;Péran et al, 2009;Yao et al, 2009). Furthermore, agerelated increase in R2* have been reported previously in the GP in some studies (Callaghan et al, 2014;Draganski et al, 2011). On the other hand, the lack of a significant age-related difference in the GP with QSM in the present study is consistent with previous post-mortem evidence (Hallgren and Sourander, 1958), and confirmed in vivo (Li et al, 2014), that iron deposition in the GP increases rapidly from birth until the second decade of life but thereafter plateaus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The high R2* values for the GP (independent of age) in contrast to thalamus, caudate and putamen are consistent with previous in vivo R2* reports and post-mortem correlations with iron concentration (Gelman et al, 1999;Langkammer et al, 2010;Péran et al, 2009;Yao et al, 2009). Furthermore, agerelated increase in R2* have been reported previously in the GP in some studies (Callaghan et al, 2014;Draganski et al, 2011). On the other hand, the lack of a significant age-related difference in the GP with QSM in the present study is consistent with previous post-mortem evidence (Hallgren and Sourander, 1958), and confirmed in vivo (Li et al, 2014), that iron deposition in the GP increases rapidly from birth until the second decade of life but thereafter plateaus.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore both aforementioned studies were limited to regions-of-interest (ROI) analyses. Yet, recent aging lifespan studies using quantitative multimodal MRI (Callaghan et al, 2014) and QSM (Acosta-Cabronero et al, 2016) have shown whole-brain analyses may be used to reveal global patterns of iron distribution that may otherwise be missed in pre-defined ROI analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Novel quantitative MRI protocols of the spinal cord and brain have the potential to measure neural changes at the microstructural level. This is because the degree of myelination, iron content and neuronal microstructure are reflected in MR relaxation times, magnetization transfer and diffusion-weighted images which can be measured at high resolution [14][15][16]. These novel quantitative MR methods include multiparametric mapping [17][18][19][20][21] and diffusion tensor imaging [22] next to volumetric measures (i.e.…”
Section: Human Spinal Cord Injury: Noninvasive Tracking Of Trauma-indmentioning
confidence: 99%
“…due to co‐localized and interacting effects of atrophy and MRI parameter changes, as occur during ageing 46. It has also been shown that age‐related atrophy and differences in tissue microstructure can be captured by the qMRI parameters used in this study 30, 46. To circumvent any atrophy‐related confound being introduced here, the cohort used was restricted to a narrow age range (18–25 years).…”
Section: Discussionmentioning
confidence: 99%
“…Significance was defined as voxels having a p value less than 0.05 after small volume and family‐wise error corrections for multiple comparisons. An explicit mask described by Callaghan et al30 was used to exclude cerebrospinal fluid voxels. Given the a priori hypothesis that GM tissue classification would be variable for deep GM structures, the statistical analysis was restricted to a central search volume focusing on these structures.…”
Section: Methodsmentioning
confidence: 99%